ESG DISCLOSURE, KEPUTUSAN INVESTASI, DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN: PERAN MODERASI CASH HOLDING - Tino Sumarno; Helma Malini; Anggraini Syahputri; Mustaruddin Mustaruddin; Anwar Azazi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study examines the effect of ESG disclosure, investment decisions, and financing decisions on firm value, with cash holdings acting as a moderating variable in the food and beverage subsector listed on the Indonesia Stock Exchange. Grounded in signaling and agency theory, the research aims to provide empirical evidence on how strategic financial and sustainability-related decisions influence market valuation. The study employs a quantitative approach using panel data regression based on 132 firm-year observations from 33 companies during the 2021–2024 period. Model estimation was conducted using the Fixed Effect Model following specification tests, while moderating effects were analyzed through interaction terms. The findings indicate that ESG disclosure and investment decisions proxied by capital expenditure have a positive and significant impact on firm value, whereas financing decisions measured by long-term debt do not exhibit a significant effect. Furthermore, cash holdings do not moderate the relationship between ESG disclosure and investment decisions with firm value; however, they significantly weaken the effect of financing decisions on firm value, suggesting the presence of financial inefficiency when liquidity is excessive. These results highlight the importance of sustainability transparency and capital allocation strategies in enhancing firm valuation while emphasizing the contextual role of liquidity management in corporate financing outcomes.